Pedagogy of Environmental Education in Federal College of Education (Technical) Omoku: Waste to Wealth in Perspective - Nwogbidi, Kingsley Chibuzor; Osaiyuwu, Rita Chinoye (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
According to this saying, that no nation can rise above the level of its teachers or those teaching them/her, this invariably or necessitates the need for encultration, pedagogy and enhanced curriculum for purposes of delivering impactful knowledge to the learners/students alike, the need to translate wastes to wealth through impactful learning, training, research and pedagogical tools cannot be over emphasized. Waste can be turned to wealth when we apply the right tools, right thinking, right education. To be exact, one can say that ingenuity occurs when opportunity meets with knowledge. It is my desire that this publication opens up further horizon for researches in similar ground breaking areas.